Researching and Innovating from the 13+ Institute for Engineering Research and Innovation - Rivas-Trujillo, Edwin (Ingeniería, 2023)
Nowadays, the changes caused by globalization, the digital revolution, and the concept of environmental sustainability, among others, have created an imperative need to strengthen society’s socioeconomic, political, cultural, and environmental structure.